DAUR HIDUP JENIS-JENIS CAPLAK INDONESIA:ARGAS(PERICARGAS)ROBERTSI HOOGSTRAAL,KAISER&KOHLS,1968(ACARINA:RGASIDAE) - HASAN BASRI MUNAF (BERITA BIOLOGI, 1986)
H B.MUNAF 1986.The life cycle of tinks of Indonesia:Argas(Persigas)robertsi Hoogstraal,Kaiser&Kohls,1986(Acarina Argasidae).Berita Biologi 3(5): 199-202.in the sequence of laboratory works in orde to fulfil the laks of biological data of ticks of Indonesia,the life-cycle of a fowl tick,argas (pericargas) robertsi, was studied. Nymphs and adults were fed on pigeons using capsule system.The completion of the life-cycle required minimum 55 days.Other observable data in this study,such as amount of eggs, percent tages of edysized ticks survivals were given.